Analisis Strategi Komunikasi Pemasaran Pedagang Pasar Untuk MeningkatkanPendapatan (Omzet) Dalam Perspektif Etika Bisnis Islam (Studi Pedagang Pasar Rakyat Aurduri Kota Jambi) - Indah Dewi Sundayani; Ridhwan .; Yusuf Zaini Aprizal (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the marketing communication strategies implemented by traders at Aurduri Traditional Market in Jambi City in an effort to increase their income (turnover), as well as to evaluate the implementation of Islamic business ethics in trading activities. This study uses a qualitative approach with in-depth interview methods and participatory observation of traders and buyers in the market. The data analysis technique used is SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in the marketing communication strategies implemented. The results of the study show that traders at Aurduri Traditional Market implement various marketing communication strategies, such as direct interaction with customers, providing discounts, and promotions through simple social media. However, the implementation of this strategy still faces challenges in the form of competition with modern markets and limited technological knowledge. From the perspective of Islamic business ethics, most traders have implemented the principles of fairness, transparency, and honesty in transactions.